Impacts of Australia's free trade agreements on trade in agricultural products: an aggregative and disaggregative analysis. (4th May 2020) - Timsina, Krishna P.; Culas, Richard J.
Abstract : The importance of free trade agreements (FTAs) has been increasing as such agreements help reduce barriers to trade. This paper estimates the agricultural trade creation and export diversion effects of Australia's free trade agreements (FTAs) at the aggregate and disaggregate levels, using the Poisson pseudo‐maximum‐likelihood (PPML) estimator. It includes 24 of Australia's major trading partner countries comprising FTA and non‐FTA members and covers 22 years from 1996 to 2017. The heteroscedasticity robust regression error specification test (RESET) confirms the relevance of PPML over the Ordinary Least Square (OLS) estimator. Results showed that China–Australia, Korea–Australia, Australia–USA and Japan–Australia have larger trade creation effects in the agricultural sector. At the commodity level, variation in trade creation effects is estimated from the different trade agreements. Among the selected commodities, the larger effects were generated in trade in sugar and wine by the implementation of the majority of the trade agreements. Overall, the trade creation was greater than the export diversion of the FTAs. The findings of the study have implications for Australia's future trade agreements.